The Effect of Mindful Learning on Senior High School Students’ English Writing Skills and Affective Engagement - Kadek Sonia Piscayanti; IGA Lokita Purnamika Utami; Ni Wayan Monik Rismadewi; I Wayan Wistiananta; Putu Ryan Hardy Kurniawan (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: This study explores the impact of mindful learning in English as a foreign language (EFL) among high school students, with a focus on affective engagement. Mindful learning techniques have gained attention for enhancing students’ focus, anxiety management, and overall academic performance; however, their effects in EFL settings have been less studied. Objective: To examine the influence of mindful learning on students’ writing skills and their engagement during the writing process in EFL contexts. Methods: The study employed a convergent parallel mixed-methods design integrated with a quasi-experimental post-test control group design. Two intact classes from a high school in Singaraja, Indonesia, were selected, with one group receiving mindful learning instruction and the other receiving conventional EFL teaching. Data were collected through post-test writing scores, classroom observations, teacher interviews, and student journals. Results: Post-test results, analyzed using an independent-samples t-test, revealed that the experimental group outperformed the control group in writing scores. Qualitative data indicated that students in the experimental group demonstrated better concentration, lower anxiety, and a more positive attitude toward their learning. Conclusion: Mindful learning significantly enhances writing competency and affective engagement among high school EFL students. This study contributes by integrating analysis of writing skills and affective engagement in the application of mindful learning within a high school EFL context.